Jaundice in newborn monitoring using color detection method - Muhammad Naufal, Mansor; Sazali, Yaacob, Prof. Dr.; Hariharan, Muthusamy, Dr.; Shafriza Nisha, Basah, Dr.; Syahryull Hi-Fi Syam, Ahmad Jamil; Mohd Lutfi, Mohd Khidir; Muhammad Nazri, Rejab; Ku Mohd Yusri, Ku Ibrahim; Addzrull Hi-Fi Syam, Ahmad Jamil; Ahmad Kadri, Junoh (Elsevier B.V., 2013)
Link to publisher's homepage at www.elsevier.com